Cutaneous wound healing: canine allogeneic ASC therapy - Enciso, Nathaly (2020)
Background Wound healing is a complex biological process comprised of a series of sequential events aiming to repair injured tissue. Adult mesenchymal stem cells (MSCs) have been used in cellular therapy in preclinical animal studies; a promising source of MSCs is adipose tissue (AT). In this paper, we evaluated the clinical value and safety of the application of cultured allogenic MSCs from AT for acute and chronic skin wound healing in a canine model. Methods Twenty-four dogs of different breeds between 1 and 10 years of age with acute and chronic wounds were studied. Morphology of the wounded skin was monitored for changes over time via serial photographs and histopathological studies. Results The percentage of the wounds that exhibited contraction and re-epithelialization were significantly different between wounds treated with adipose mesenchymal stem cells (ASCs) and control wounds; this effect was observed in both acute and chronic conditions. At 90 days, re-epithelization of acute and chronic wounds reached more than 97%. Histopathological study revealed a reduction in inflammatory infiltrate and the presence of multiple hair follicles on day 7 after treatment with ASCs, promoting epidermal and dermal regeneration. To guarantee the safety of our treatment, we determined the serum levels of cytokine markers in our patients. ASC treatment upregulated granulocyte-macrophage colony stimulating factor (GM-CSF) at the gene level, which may contribute to the recruitment of cells that participate in skin repair to the site of injury. Conclusions The development of an allogenic ASC therapy to improve wound healing in a canine model could have a clinical impact in human treatment.